HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP WUS TERHADAP PERILAKU PEMERIKSAAN PAYUDARA SENDIRI (SADARI) - Ekanita, Pipit; Khosidah, Amik (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
ABSTRACT: RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES OF WOMEN OF CHILDBEARING AGE TOWARD BEHAVIOUR OF BREAST SELF EXAMINATION (BSE). One of the early detection breast cancer is Breast Self-Examination (BSE). The main problem is the irregularity of breast cancer and breast self-exam is rarely done correctly. Correctional activities of BSE for all women of childbearing age began, because 85% of abnormalities in the breast it was first discovered when a patient identified by mass screening is not performed. Objectives: Determine the relationship between knowledge and attitudes of women of childbearing age toward behavior of BSE in Banteran Village Wangon District Banyumas Regency. Methods: This study uses survey research cross sectional analytic approach. The subject of this study is women of childbearing age to the amount of 93 people are taken by random cluster sampling. The instrument was used questionnaire. Analysis of the data used is univariate (calculating percentages) and bivariate (Spearman Rank). Results: research results obtained knowledge of women of childbearing age about BSE mostly with good knowledge of the category as many as 40 respondents (43%), attitudes of women of childbearing age in did most of the categories of BSE was not a good attitude even as many as 59 respondents (63.44%), behavior of women of childbearing age in did most of the categories of BSE was never as much as 46 respondents (49.5%), there was a relationship between knowledge of women of childbearing age with behavior of BSE, and there was a relationship between attitudes of women of childbearing age with behavior of BSE. Conclusion: There is a relationship between knowledge and attitudes of women of childbearing age towards the behavior of breast self examination. Suggestions: For health official, expected to increase information about BSE, so it can make to increase the knowledge of women of childbearing age about the importance of breast self and can increase the attitude of women of childbearing age doing breast self-exam.Keywords: Knowledge, Attitude, Behaviour BSE.